Comparison of characteristics between Chinese diabetes mellitus-induced erectile dysfunction populations and non-diabetes mellitus-induced erectile dysfunction populations: A cross-sectional study - Peng, Jingxuan; Li, Dongjie; Liu, Longyun; Xiang, Yali; Tang, Yuxin (Frontiers in Endocrinology, 2022)
Background: Erectile dysfunction (ED) is a common disease in adult men, and diabetes is an independent risk factor for ED. However, there are few reports on the distinction between diabetes mellitus-induced erectile dysfunction (DMED) and non-DMED features, as well as ED features of varying severity in the two groups. Methods: A total of 365 ED patients treated at two clinics in China from 2019 to 2022 were included. Questionnaires of the International Index of Erectile Function (IIEF-5), Erectile Hardness Score (EHS), Premature Ejaculation Diagnostic Tool (PEDT), Patient Health Questionnaire-9 (PHQ-9), and Generalized Anxiety Disorder-7 (GAD-7) were administered to the patients. They were divided into three groups according to the IIEF-5 score: 5-7 for severe ED, 8-11 for moderate ED, and 12-21 for mild ED. In addition, the patient's age, weight, height, fasting blood glucose (FBG), total cholesterol (TC), triglycerides (TG), follicle-stimulating hormone (FSH), luteinizing hormone (LH), prolactin (PRL), total testosterone (TT) and other indicators were also collected. Statistical analysis was performed using SPSS 26, comparing all parameters between groups. Results: Age (P<0.001), height (P=0.009), body mass index (BMI) (P=0.002), PEDT (P<0.001), FBG (P<0.001), FSH (P<0.001),TG (P<0.001), TT (P<0.001) and triglyceride-glucose index (TyG) (P<0.001) were significantly different between diabetic ED and nondiabetic ED subjects. The trend test in the nondiabetic ED population found a negative correlation between the IIEF-5 score and PHQ-9 (P for trend=0.15). Multivariate ordinal logistic regression in the diabetic ED population showed that elevated LH OR=11.37 (95% CI: 0.966, 3.897) and elevated PRL OR=4.10 (95% CI: 0.410, 2.411) were associated with an increased risk of more severe ED. Conclusions: The aetiology, demographic parameters, degree of premature ejaculation, and related biochemical tests were significantly different between the DMED and non-DMED populations.